Experimental Quantification of Local Pressure Loss at a 90° Bend in Low-Pressure Dilute-Phase Pneumatic Conveying of Coarse Particles - Rui Zhu; Chunsheng Luo; Xin Li; Fei Yan (International Journal of Chemical Engineering)
Focusing on the insufficient estimation of the local pressure loss at a 90° horizontal-vertical bend in low-pressure pneumatic conveying of coarse particles, experiments are conducted in a 80 mm inner diameter test bend by using polyethylene particles having an equivalent spherical diameter of 4.00 mm. The influences of the local pressure loss versus the gas flow Reynolds number, the solid-gas ratio, and the bending radius ratio are investigated. Based on the additional pressure theory of Barth, an empirical formula estimating the local pressure loss is obtained using dimensional and nonlinear regression analysis. Summarizing the experiments and literature, the results expound on the local gas flow pressure loss coefficient decreases with increasing Reynolds number, and first decreases and then increases with increasing bending radius ratios from 0.5 to 7. The additional solid flow pressure loss coefficient decreases with the increasing Reynolds number and bending radius ratio in the dilute phase, and linearly increases with increasing solid-gas ratio. Compared with the estimated values with the experimental values, the calculated standard deviation is below 4.11%, indicating that the empirical formula can be used to predict local pressure loss at the bend in the low-pressure dilute-phase pneumatic conveying.